Big data analysis and changes in customer preferences in post-pandemic global tourism - N. A. Zamyatina (Вестник университета)
The list of leading big data holders, whose market intelligence has the most authority for forecasting and planning in global tourism, as well as the reports based on big data analysis are of high importance to be verified. The study reveals a lack of attention to the big data potential for forecasting in tourism and use of traditional limited methods of consumer preferences research published in the annual reports and then circulate in media. Nevertheless, big data analysis implemented by various companies reflects a dramatic change in consumer priorities of the post-pandemic period and captures the demand for authenticity, variety, increased concern for physical and mental health, intangible luxury, and, in general, understanding that traveling is beginning to be perceived as one of essentials of healthy lifestyle. Given these limitations, the list of consumer preferences based on the reported tourism trends for 2023 is of practical relevance to all stakeholders in the industry.